Effects of Coal Blending and Operating Conditions on Combustion and NOx Emission Characteristics in a Tangentially-fired Utility Boiler. (May 2017) - Li, Debo; Lv, Qiang; Feng, Yongxin; Wang, Chang'an; Liu, Xuan; Chen, Kai; Xu, Kai; Zhong, Jun; Che, Defu
Abstract: The influences of operating conditions, such as excess air ratio and SOFA arrangement, on temperature distributions, species distributions, NO x emissions and burnout of a tangentially-fired utility boiler using bituminous and blended coal were investigated by numerical approach in the present study. The simulation results show that the fuel type exhibits certain effect on the temperature distributions and the NO x emissions. Moreover, higher excess air ratio could restrain the CO formation but promote NO x emission. The temperature and the species distributions are highly related to the SOFA arrangement. In addition, SOFA technology is still an effective approach to control the NO x emissions during blended coal combustion, while the disadvantageous effect on char burnout should be considered.